Active ingredients isolated from Periplaneta americana L. inhibit the inflammation of the colonic mucosa and regulate the gut microbiota in DSS-induced ulcerative colitis in mice - Wang, Yanhuan; Ni, Fa; Wu, Genrui; Xiao, Huai; Yang, Zhibin; Zhang, Chenggui; Zhao, Hairong; Liu, Heng (Frontiers in Pharmacology, 2025)
IntroductionUlcerative colitis (UC) is a chronic inflammatory bowel disease characterized by colonic mucosal inflammation, compromised intestinal barrier function, and gut microbiota dysbiosis. Current therapies often have significant limitations, including adverse effects, highlighting the need for safer alternatives. Periplaneta americana L. (PA), documented in Shennong's Herbal Classic, possesses anti-inflammatory, tissue-repairing, and immunomodulatory properties. While previous studies demonstrated efficacy of PA in rodent UC models generated using different inducers, the active components within aqueous extracts (PAW) and their comparative effects remain unclear.MaterialsTo address this gap, this study investigated the composition and therapeutic activity of PAW and its sequentially fractionated components based on molecular weight: PAW1 (< 3 kDa), PAW2 (3-10 kDa), and PAW3 (> 10 kDa) using membrane separation. Using a dextran sulfate sodium (DSS)-induced UC model in C57BL/6 mice, we compared the effects of unfractionated PA and its fractions (PAW1, PAW2, PAW3) on UC pathology and intestinal flora.ResultsOur results demonstrate that PA, PAW1, PAW2, and PAW3 ameliorated key UC-associated pathologic features; notably, the unfractionated PA exhibited superior efficacy compared to its individual fractions. PA treatment significantly mitigated DSS-induced body weight loss, disease activity index scores, and colon shortening. It preserved intestinal mucosal integrity, evidenced by increased goblet cell numbers and elevated expression of tight junction proteins (occludin-1, ZO-1). PA treatment reduced colonic inflammation by significantly downregulating pro-inflammatory mediators (NF-κB-p65, TLR4, MyD88, TNF-α, IL-17A, IFN-γ, MPO, iNOS) and upregulating the anti-inflammatory cytokine IL-10, while IL-4 levels were also modulated. Furthermore, PA treatment attenuated intestinal dysbiosis in UC mice, characterized by an increase in beneficial bacteria (e.g., Psychrobacter) and a decrease in taxa like Actinobacteriota.ConclusionThese findings collectively indicate that the aqueous extract of Periplaneta americana L. and its fractions possess significant therapeutic potential for UC treatment, with the unfractionated extract showing the most pronounced benefits via modulating inflammation, restoring barrier function, and rebalancing gut microbiota.